Common variation at 3p22.1 and 7p15.3 influences multiple myeloma risk. - Broderick, P; Chubb, D; Johnson, D; Weinhold, N; Försti, A; Lloyd, A; Olver, B; Ma, Y; Dobbins, SE; Walker, B; Davies, F; Gregory, W; et al. (2012)
To identify risk variants for multiple myeloma, we conducted a genome-wide association study of 1,675 individuals with multiple myeloma and 5,903 control subjects. We identified risk loci for multiple myeloma at 3p22.1 (rs1052501 in ULK4; odds ratio (OR) = 1.32; P = 7.47 × 10(-9)) and 7p15.3 (rs4487645, OR = 1.38; P = 3.33 × 10(-15)). In addition, we observed a promising association at 2p23.3 (rs6746082, OR = 1.29; P = 1.22 × 10(-7)). Our study identifies new genomic regions associated with multiple myeloma risk that may lead to new etiological insights.